Thymic stromal lymphopoietin-stimulated CD4+ T cells induce senescence in advanced breast cancer - Boieri, Margherita; Marchese, Emanuela; Pham, Quan Minh; Azin, Marjan; Steidl, Lauren E.; Malishkevich, Anna; Demehri, Shadmehr (Frontiers in Cell and Developmental Biology, 2022)
Thymic Stromal Lymphopoietin (TSLP) plays a prominent role in inducing type 2 immune response, commonly associated with atopic diseases. TSLP-activated CD4+ T helper 2 cells block early carcinogenesis by inducing terminal differentiation in spontaneous breast and lung cancer models. However, the impact of TSLP induction on advanced cancer with altered cellular phenotypes is unclear. Using an established MMTV-PyMttg breast cancer cell line, we demonstrate that TSLP-stimulated CD4+ T cells possess an antitumor effect in advanced breast cancer. In contrast to early breast cancer suppression, the antitumor immunity mediated by TSLP-stimulated CD4+ T cells in advanced breast cancer is mediated by the induction of a senescent-like phenotype in cancer cells. Inflammatory CD4+ T cells drive breast cancer cells into senescence by releasing interferon-gamma and tumor necrosis factor-alpha, which directly bind to their receptors on cancer cells. Our findings reveal a novel mechanism of TSLP-activated CD4+ T cell immunity against advanced breast cancer, mediated by cellular senescence as a distinct effector mechanism for cancer immunotherapy.